The Application of Sputtered Gallium Oxide as Buffer for Cu(In, Ga)Se2 Solar Cells. Issue 9 (14th July 2021) - Witte, Wolfram; Paetel, Stefan; Menner, Richard; Bauer, Andreas; Hariskos, Dimitrios
Abstract : Crystalline gallium oxide is a promising wide‐bandgap semiconductor material, especially for applications in high‐frequency and high‐power devices. With an optical bandgap energy well above 4 eV, which implies no visible light absorption, it is also a candidate for one of the front‐side layers in thin‐film solar cells. X‐ray amorphous gallium oxide (a‐Ga2 O3 ) deposited by RF magnetron sputtering is applied as an n‐type buffer layer in substrate‐type configuration solar cells based on industry‐relevant inline coevaporated Cu(In, Ga)Se2 (CIGS) absorbers, which include an i‐ZnO/ZnO:Al bilayer as the front electrode. The cells exhibit an efficiency peak at Ga2 O3 deposition temperatures in the range of 140–180 °C and show mostly a gain in short‐circuit current density compared with the CdS‐buffered reference cells, as a result of the high optical bandgap of a‐Ga2 O3 in the range of 4.6–4.8 eV. The CIGS solar cells with sputtered a‐Ga2 O3 buffers reach efficiencies of almost 14%, lacking in open‐circuit voltage and fill factor, whereas the CdS‐buffered cells are on a 16–17% level. Light soaking of the cells leads to a slight improvement of the fill factor, but the gap in open‐circuit voltage of 80–100 mV in contrast to the CdS‐buffered reference cells remains unaffected. Abstract : The application of X‐ray amorphous gallium oxide (a‐Ga2 O3 ) deposited by RF magnetron sputtering as buffer layer for Cu(In, Ga)Se2 (CIGS) thin‐film solar cells is described. The a‐Ga2 O3 buffers exhibit a high optical bandgap energy well above 4 eV and corresponding CIGS solar cells reach power conversion efficiencies up to 13.7%, strongly depending on deposition temperature during sputtering.